Data management system: A guideline on data consolidation for OBE CDL reports / Asmidar Alias … [et al.] - Alias, Asmidar; Zainul Rashid, Zarina; A Halid, Rozieana; Osman, Maziana; Karim, Mariathy (2012)
The implementation of Outcome-Based Education (OBE) in UiTM has reached its final stages at which every academic programme is required to carry out an evaluation on its performance based on several criteria. In conventional practice, the evaluation is usually made on the basis of students' performance in tests and examinations. However, with the introduction of OBE, specifically the reporting system known as OBE-CDL report, students grades are not the sole criterion in determining the success of an academic programme, but other criteria have been included to form the basis of evaluation. These criteria include teaching performance, entrance and exit survey, and assessment on the alignment of course information and delivery, to name a few. However, the committee in charge of preparing the OBE CDL reports for every programme and unit have experienced difficulties in gathering the data and this affects the process of consolidating data for the report. As such, there is a dire need for a systematic approach in consolidating the data for the report. This paper examines the difficulties experienced by faculties and OBE Committee in completing the report on time as requested by the Division of Academic and International Affairs (Bahagian Hal Ehwal Akademik dan Antarabangsa, HEM). A guideline on data management system to consolidate data for the report is proposed to alleviate difficulties and minimize complexity during collecting data and reporting. The processes, approach, specific requirement involved for this exercise are discussed, which highlight the salient aspects of the problems.